Planetary nebulae as tracers of accreted stellar populations in massive galaxies in groups and clusters - Hartke, Johanna (Frontiers in Astronomy and Space Sciences, 2025)
Planetary nebulae (PNe) are valuable spatial and kinematic tracers of nearby galaxies. In this mini-review, I focus on their role in tracing the halo and intra-cluster/intra-group light assembly in groups and clusters of galaxies within 100 Mpc and, in particular, the link between characteristic PN metrics such as the α-parameter and the PN luminosity function and changes from the underlying in situ to ex-situ stellar populations. These results from nearby groups and clusters are placed into context with integral-field spectroscopic surveys of galaxies, which allow the co-spatial measurement of PN and stellar population properties. I provide an outlook on upcoming instrumentation that will provide new opportunities for the study of extragalactic PN populations. I address the challenges of reconciling observations of extragalactic PN populations with predictions from stellar evolution models and how revised late-stellar-evolution models have alleviated some of the tensions between observations and theory.